Upaya Peningkatan Keterampilan Bermain Drama Dengan Menggunakan Teknik Oscar Brocket Pada Siswa Kelas XI SMA Negeri 6 Palembang - Oktaviani, Anis; Lestari, Hikmah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine learning outcomes by improving drama playing skills using the Oscar Brocket technique for class XI students at SMA Negeri 6 Palembang. In this research, data collection used test techniques. This increase in score shows that the implementation of actions in cycle I and cycle II was able to improve students' drama playing skills. The application of the Oscar Brocket technique is also able to provide motivation and enjoyment in the process of learning to play drama. Students look more enthusiastic and enthusiastic when playing drama. Before the implementation of the action, students still did not dare to express themselves, were less active, often joked with other students, and students still seemed hesitant to play the characters they presented so that the roles they played were less than optimal. After implementing the action, students become more expressive, more active, the learning process becomes conducive, and students no longer hesitate in playing the characters they present, students are even able to improvise in playing the characters.